Emergence of resistance to ciprofloxacin inNeisseria meningitidisin Brazil. Issue 3 (March 2018) - Gorla, Maria Cecília; Cassiolato, Ana Paula; Pinhata, Juliana Maira Watanabe; de Moraes, Camile; Corso, Alejandra; Gagetti, Paula; Lemos, Ana Paula
Abstract : N/A: To prevent secondary invasive meningococcal disease (IMD) cases and outbreaks, antimicrobial prophylaxis of high‐risk contacts is indicated. This study reports two ciprofloxacin‐resistant Neisseria meningitidis strains in Brazil. The 3523 N. meningitidis isolates collected throughout Brazil from 2009 to 2016 were evaluated for antimicrobial resistance. Meningococcal isolates showing minimal inhibitory concentrations, MICs≥0.125μg ml −1 to ciprofloxacin, were analysed to determine the presence of mutations in the quinolone resistance‐determining regions (QRDRs) of gyrA and parC genes. Two ciprofloxacin‐resistant N. meningitidis isolates were found, both presenting a single mutation in the quinolone resistance‐determining region of the gyrA gene. These results confirmed that ciprofloxacin is still a first‐line drug for chemoprophylaxis. However, we highlight the importance of continued surveillance to monitor the trends of N. meningitidis susceptibility profiles to the antimicrobials recommended for chemoprophylaxis and IMD treatment.